Online Real Estate Management System / Rajasekar Swaminathan - Rajasekar, Swaminathan (2004)
In the year 2000, there was a drastic demand for new property in Malaysia. With the astonishing growth of the Internet, real estate companies are beginning to find new ways to expand their businesses as Internet and E- commerce has given businesses the ability to interact closely with end consumers. Online real estate is expected to meet the increasing demands for the new properties. Online Real Estate Management System is a development of an automated system for property-related service on the Internet. This project is aimed at developing a web based online real estate application. With this system, real estate agents, potential buyers, sellers, landlords, and other parties in real estate dealings can easily collaborate in a secure Web environment. This automation uses e-commerce to increase buyers' utility through information accessibility and efficiency in real estate dealings compared to the traditional business approach. The main features of this website would be post and view property listings; search for commercial, industrial, and residential property; and calculate loan amount. Features mentioned above are expected to speed up the buying and selling process; provide an easier, convenient and faster mode for finding relevant details about commercial, industrial, and residential properties for rent or for sale; promote online property advertising and listings; and provide the user with unsurpassed service and content when it comes to shopping for property online.